DIGITAL TRANSFORMATION MANAGEMENT IN ISLAMIC EDUCATIONAL INSTITUTIONS: ADAPTATION STRATEGIES FOR THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 AND 5.0 - Gita Aryani (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Digital transformation is both a challenge and an opportunity for Islamic educational institutions in facing the dynamics of the Industrial Revolution 4.0 and Society 5.0. This study aims to analyze the digital transformation management strategies implemented by Islamic educational institutions in improving the effectiveness of governance and learning quality. The research method used is a qualitative approach with the library research method, which is by examining various literature and the latest research results that are relevant to the topic of digital transformation and Islamic education management. The results of the study show that the success of digital transformation is determined by three main aspects, namely visionary leadership based on Islamic values, strengthening the digital literacy of educators and education personnel, and integrating information technology systems in the management of educational institutions. In addition, it was found that Islamic educational institutions that are able to adapt strategically to technological changes have higher competitiveness in creating an effective, innovative, and characterful learning ecosystem. The conclusion of this study emphasizes the importance of synergy between spiritual values and technological innovation in realizing globally competitive Islamic education in the digital era.